The spirit of Zoroastrianism - Skjærvø, Prods O. (The sacred literature series, 2011)
Zoroastrian literature. Background ; The Avesta and other Zoroastrian literature -- Creation and the Divine World. Cosmic contrasts and the two spirits ; Order and chaos ; Creation ; Gods ; Demons ; The creation of living beings -- Mythical history and the Zarathustra myth. Hero-sacrificers of the first ages -- Eschatology and the End of the World -- Body and soul -- Death, rewards, and punishment --Ethics -- Rituals. The Yasna, a ritual re-creation of the world ; The Videvdad, a ritual purification of the world -- On kingship -- Doctrinal issues -- Translations. Texts on the history of the Sacred Tradition ; Texts on creation and the Divine World ; Texts on mythical history ; Texts on eschatology and the End of the World ; Texts on body and soul ; Texts on death, rewards, and punishment ; Texts on ethics ; Ritual texts ; Texts on kingship ; Texts on doctrinal issues